WORKING CAPITAL AND PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN KWARA STATE, NIGERIA - JOEL ABOYEJI ARANSIOLA (Malete Journal of Accounting and Finance)
Small and medium scale enterprises are the engine room of any nation’s development, yet, this sector is bedeviled by several constraints including poor working capital management practices which continue to mar its developmental objectives. Hence, this study evaluates the impact of working capital management on the performance of small and medium scale enterprises in Kwara State, Nigeria. The study was carried out using primary data which was obtained through the administration of copies of questionnaire to owners and senior management staff of small and medium scale enterprises in Kwara state. The data were analysed using descriptive statistics, structural equation model and ordered logit regression. The findings of the study reveal that frequently used working capital are personal savings, profit from the business operations, bank loans and account payable. The study also reveals that cash management practices significantly impact on the performance of small and medium scale enterprises in Kwara state with a coefficient value of 1.575421 at a 1% significance level while account receivables practices also significantly impact on the performance of small and medium scale enterprises in Kwara state, with a coefficient value of .6241527 at 5% significant level. It was further revealed from the study that inventory management practices are a significant determinant of performance of small and medium scale enterprises in Kwara state with a coefficient value of 3754485 at a 5% significance level. Finally, it was revealed that account payable practices are significant determinants of performance of small and medium scale enterprises in Kwara state with a coefficient value of .5051616 at a 5% significance level. The study concluded that working capital management significantly influences the performance of small and medium scale enterprises in Kwara state. Based on the findings, it is suggested that management of SMEs should pay attention on reducing the number of day’s accounts receivable and inventories to a reasonable minimum to generate enough profitability for owners and shareholders.